The regulation of Sox3 function in zebrafish embryonic development - Lam, Chi Man (2016)
Embryogenesis in vertebrates is regulated by highly complicated signaling networks, which involve various signaling pathways and factors. Sox3 is known to have critical roles during the whole of embryonic development in vertebrates. In zebrafish, it has been shown that Sox3 restricts organizer formation as well as inhibiting Fgf signaling, which is required for the expression of organizer genes. On the other hand, SUMOylation has been suggested to be a regulator of the transcriptional activity of Sox3. The SUMOylaton has previously been demonstrated on mouse Sox3 and chick Sox3. In this study, I examined the role and regulation of Sox3 in early embryogenesis in zebrafish. In the first part of the study, I inspected the detailed expression of gsc and chd, in comparison to foxd3 expression. It was demonstrated that Sox3 and Fgf signaling could repress both gsc and chd independently from each other. Sox3 was also found to be able to directly act on the promoter region of gsc. In the second part of the study, it was shown that the SUMOylation of Sox3 appeared to occur in zebrafish embryos. The SUMOylation of Sox3 was also shown to correlate with the chromatin fraction, although there was a very small fraction of Sox3 SUMOylated. The biological effect of SUMOylation of Sox3 has also been analysed. It was shown that SUMOylation of Sox3 could enhance the transcriptional repressor activity of Sox3. The result of luciferase reporter assay on the promoter region of boz also suggested that SUMOylation eliminated the transcriptional activator activity of Sox3. These data raise the possibility that SUMOylation of Sox3 might act as the switch from a transcriptional activator to a repressor.